Hey Fellows, We Shrunk the Server - Sousa, Valentim; Ferreira, Paulo; Gericota, Manuel (International Journal of Online and Biomedical Engineering (iJOE), 2012)
Remote laboratories are an essential part of Web-based engineering lecturing, enabling future engineers 24/7 access to lab resources. Furthermore, they allow sharing expensive resources among multiple universities and research centres. Typical remote lab architectures feature a server, normally a computer that may serve one or more experiments. Computers are generally bulky, somewhat expensive and require heavy resources to run complex operating systems. In this paper, a remote lab for the test of printed circuit boards and the programming/configuration of programmable logic devices and memories through a JTAG interface is presented. This lab is based on open source software and on a cheap router with OpenWrt firmware, a Linux distribution targeted at embedded systems, which acts as a processing unity. A router acting as a server is not a common solution in remote labs. When compared to a â??normal